THE EFFECT OF NARROW MONEY (M1), BROAD MONEY (M2) AND EXCHANGE RATE ON PROFITABILITY OF KBMI 1 AND 2 BANKS - Simbolon, Ika Pratiwi; Panjaitan, Raya; Angelia, Nia (SULTANIST: Jurnal Manajemen dan Keuangan, 2024)
The aim of this research is to analyze the effect of narrow money (M1), broad money (M2) and exchange rates on the profitability of KBMI 1 and 2 banks. This research is quantitative research that relies on numerical data. This study is crucial to deliver valuable informations to investors and management of company. The method of data analysis in this paper is carried out quantitatively which will be measured using statistics through SPSS version 27. The data used in this study is secondary data from January 2018 - December 2023 at KBMI 1 and 2 banks. Based on this study, it can be summarized that M1 and M2 have significant effect to ROA for KBMI 1 Banks. Exchange rate has significant effect to ROA for KBMI 2 Banks. The monetary authority really needs to maintain economic stability by making good monetary policy. This will also have an impact on increasing profitability in the banking sector in Indonesia. The findings of this study can help investors, policy makers, and other stakeholders in making decision and improving the bank performance in the future. This study has several limitations, there’s no investigation further of Return on Asset of the other countries such as developing and developed countries. Researchers who want to conduct research with the same theme are expected to use other variables more specific to Return on Asset. It is hoped that further research will pay attention to other factors that can effect Return on Asset of banking companies.